Application of Cleaner Production in a Fruit Chips Industry - Hadi, Danang Kumara; Putri, Rizka Aidina; Farida, Siska Nifroatul; Santoso, Imam (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
Abstract Cleaner production (CP) is one of the sustainable implementations of a comprehensive preventive environmental strategy involving company processes, products, and services. CP plan implementation still faces obstacles, such as the lack of detailed information, tools, and techniques. This study aimed to determine the variables and to select alternative solutions for cleaner production at a fruit chip industry using the Analytical Hierarchy Process (AHP) method. The research was carried out at PT Agrijaya Indotirta in Malang, East Java. The production process at this company generates waste from the consumption of energy, water, materials, and raw materials. Energy and water consumption are disposed directly without preliminary recycling process. Used oil is sold, and the remaining fruit seeds are sold for seeds. Checklists are used for problem identification, while fishbone diagrams and the 5W1H method are used to solve the problem of getting the best solution from the available alternatives. The weighting results of the alternative solutions using the AHP method show that the application of Good Manufacturing Practice (GMP) (with a weight of 0.287080) on the human resource criteria (with a weight of 0.63699) is a suitable alternative solution for the CP application of fruit chips production at PT Agrijaya Indotirta. Cleaner production can be performed by improving the capacity of human resources as production actors and regulators of proper waste management.Keywords: Analitycal Hierarchy Process, cleaner production, fruit chips, waste handling AbstrakSalah satu implementasi berkelanjutan dari strategi lingkungan preventif komprehensif yang melibatkan proses, produk, dan layanan perusahaan adalah penerapan cleaner production (CP). Implementasi rencana CP masih menghadapi kendala, seperti informasi yang kurang rinci, alat, dan teknik. Tujuan penelitian ini untuk menentukan variabel dan pemilihan alternatif solusi cleaner production pada produksi keripik di sebuah industri keripik buah dengan menggunakan metode Analitycal Hierarchy Process (AHP). Penelitian dilakukan di PT Agrijaya Indotirta, Malang, Jawa Timur. Proses produksi pada perusahaan tersebut menghasilkan limbah dari konsumsi energi, air, material, dan bahan baku. Konsumsi energi dan air dibuang langsung tanpa daur ulang. Material berupa minyak dijual dan sisa bahan baku berupa biji buah dijual untuk bibit. Identifikasi masalah dilakukan menggunakan daftar periksa, sedangkan pemecahan masalah dilakukan menggunakan diagram fishbone dan metode 5W1H untuk memperoleh alternatif solusi. Hasil penilaian bobot alternatif solusi dengan metode AHP menunjukkan bahwa penerapan Good Manufacturing Practice (GMP) (dengan bobot 0,287080) pada kriteria sumber daya manusia (dengan bobot 0,63699) merupakan alternatif solusi yang sesuai untuk aplikasi CP produksi keripik buah di PT Agrijaya Indotirta. Cleaner Production dapat dilakukan dengan cara peningkatan peran sumber daya manusia sebagai pelaku produksi dan sebagai pengatur penanganan limbah yang tepat.Kata kunci: Analitycal Hierarchy Process, cleaner production, keripik buah, penanganan limbah